Growth and plant-water relations of sweet potato (Ipomea batata) as affected by soil moisture regimes - Ghuman, B.S.; Lal, R. (1983)
Effects of four water table (WT) depths (15, 30, 50, and 70 cm below the soil surface) were compared with a free draining control and with transient and continuous flooding for growth and plant-water relations of two sweet potato cultivars, TIS 2148 (C-1) and TIS 2295 (C-2). Cultivar C-1 accumulated significantly more dry matter at 101 days after planting for transient flooding (TF) in comparison with WT15, WT50, WT70, and freely drained control treatments. Cultivar C-2 produced less dry matter than C-1 and its dry matter production was also more for TF compared with WT15 and free draining control. At 137 days after planting, however, the maximum above ground dry matter production was observed in WT70 for C-1 and in TF treatment for C-2 cultivars. The maximum tuber yield was obtained in WT15 and WT50 treatments, whereas tubers in the TF treatment were partly decomposed and rotten. No tuber yield was obtained in continuous flooding treatment for 14 consecutive days. Leaf water potential and leaf diffusive resistance were also affected by soil moisture regimes.